FIND OF SYNGENETIC BARIUM SULFATE IN THE PRECAMBRIAN OF THE BALTIC SHIELD - Melezhik V.A.; Fetisova O.A. (My University, 1989)
In 1985, primary sedimentary sulfates were discovered in Precambrian deposits of the Baltic Shield. The search for sedimentary sulfates was based on previous identification of the protoevaporite character of certain early Proterozoic sedimentation basins and systematic lithologic and geochemical investigations of metamorphosed sedimentary sequences that made use of improved methods of chemical analysis, allowing separate determination of total sulfur, sulfide sulfur, and sulfate sulfur. Rocks containing sulfate sulfur in concentrations significantly greater than 0.1 percent by weight were found in the sedimentary sequence of the Umba Formation in the Imandra-Varzuga zone. The sulfate-containing sequence is part of the Proterozoic (Karelian) volcanosedimentary complex which correlates, in time of origin, lithological and geochemical characteristics, plus distinctive makeup, with the Jatulian deposits of Karelia. The sequence is 50 to 150 m thick and can be traced for 130 km along the strike of the zone. Significant concentrations of sulfate sulfur were found only in the chemogenic metacarbonate and metasiliceous (jasperoid) deposits, where it coexists with high concentrations of barium. Significantly, high concentrations of Ba and sulfate sulfur are found along the entire lateral extent of the sequence. The pronounced stratigraphic and lithologic control over the distribution of barite-containing rocks, the conformal bedding of the sulfate-bearing metasilicite and crystalline carbonate rocks with the retention of the primary bedding indicate that the barite is primary and sedimentary.
Keywords: Precambrian; Precambrian; Докембрий